Ketahanan Duduk Anak Autisme Dapat Ditingkatkan Dengan Bermain Maze - amnel, hasnah sri putri (journal of residu, 2019)
This research is done to the children of autism who sit in the III Kalas in SLBN 1 Painan that there is a problem in the endurance level of sitting. The goal of the study is to increase the resilience of sitting on autism children in the learning process through playing the maze. The method in this study used an experimental approach in the form of Single Subject Research (SSR) with A-B-A design. Appraisal is instituted in the learning process which is useful to know the length of duration (time) on the endurance of sitting autism children. Data collection is derived from direct observation using graph visual data analysis. Hypotheses in this study are playing the maze can increase the endurance of sitting children autism. The results of this research show playing maze can increase the endurance of sitting children Y Autism Class III at SLBN 1 Painan.